SANKSI PENGEMBALIAN KERUGIAN KEUANGAN NEGARA BAGI KORUPTOR BERDASARKAN ASAS LEX SPECIALIS SISTEMATIS - Amalia, Wilda (SIYASI: Jurnal Trias Politica, 2023)
The issue of corruption in Indonesia has become a very tough problem to eradicate. A culture that has been rooted from generation to generation where state financial losses are dredged up. Various programs are created in the name of people's welfare but in fact create opportunities for personal enrichment. So far, sanctions for corruptors have not found a bright spot in creating clean institutions and countries. Starting from prison sanctions, to impoverishing corruptors still gives doubts whether the purpose of punishment to provide a deterrent effect has been realized. So that then raises another option whether the sanction of returning state financial losses can bring more benefits or still not. Departing from this, this article aims to examine more deeply the element of state financial losses in corruption cases by looking at the judges' considerations in deciding corruption cases. Then by examining and trying to construct the principle of lex specialist systematic as a legal reference in determining the verdict of returning state financial losses for perpetrators of corruption.Persoalan korupsi di Indonesia sudah menjadi persoalan yang begitu alot untuk di berantas. Budaya yang sudah mengakar dari generasi kegenerasi dimana kerugian keuangan negara dikeruk secara habis-habisan. Berbagai macam program diciptakan dengan atas nama kesejahteraan rakyat namun nyatanya malah menciptakan peluang memperkaya pribadi. Sejauh ini pemberian sanksi bagi koruptor tidak ditemui titik terang dalam menciptakan lembaga dan negara yang bersih. Mulai dari sanksi penjara, hingga memiskinkan koruptor masih memberikan keraguan apakah tujuan dari penghukuman untuk memberikan efek jera sudah terealisasikan. Sehingga kemudian memunculkan opsi lain apakah dengan pemberian sanksi pengembalian kerugian keuangan negara lebih dapat mendatangkan kemanfaatan atau tetap tidak. Berangkat dari hal tersebut untuk itu artikel ini bertujuan mengkaji lebih mendalam unsur kerugian keuangan negara pada kasus korupsi dengan melihat pertimbangan hakim dalam memutus perkara korupsi. Kemudian dengan menelaah dan mencoba mengkonstruksikan asas lex specialis sistematis sebagai acuan hukum dalam penetapan vonis pengembalian kerugian keuangan negara bagi pelaku korupsi.